A competing risk analysis of death patterns in male genitourinary cancer. Issue 4 (4th April 2019) - Bhattacharjee, Atanu; Roy, Gaurav; Budukh, Atul; Dikshit, Rajesh; Patil, Vijay M.; Joshi, Amit; Noronha, Vanita; Prabash, Kumar; Roy, Papai
Abstract: Background: Early diagnosis and improved therapeutic options have contributed to prolonged survival in male genitourinary cancer. However, these cancer survivors may die due to other causes. Aims: This work is aimed to explore the death patterns among male genitourinary cancer patients due to other causes. The occurrence of death not related to cancer is defined as competing risk (CR). Methods and results: Data extracted between 1973 and 2014 for male patients (n = 638 393) diagnosed with genitourinary cancer and registered in the Surveillance, Epidemiology, and End Results (SEER) Program were included for analysis. A CR analysis was performed to explore the death patterns due to cancer or otherwise. Our study evidenced a huge proportion of patients' death due to associated factors including but not limited to cancer. Interestingly, the computed hazard ratios obtained in cancers of male organ sites such as prepuce, glans penis, penis, and spermatic cord were 1.28 (0.98‐1.67), 1.53 (1.33‐1.77), 1.35 (0.19‐1.53), and 1.57 (1.24‐2.0), respectively. However, the hazard ratios evaluated on factors other than cancer in the same organ sites were 0.95 (0.76‐1.18), 1.14 (0.99‐1.3), 1.09 (0.97‐1.22), and 1.12 (0.86‐1.46), respectively. Conclusion: This study shows that among the male genitourinary cancer patients, the significant proportion of deaths occurs due to reasons unrelated to cancer. It can be concluded that the magnitude of death due to only genitourinary cancer is minimal and is not as high as documented in the earlier literature.